FORMULATION OPTIMIZATION OF PROMETHAZINE THEOCLATE IMMEDIATE RELEASE PELLETS BY USING EXTRUSION-SPHERONIZATION TECHNIQUE - S., Shelar Vishwas; V., Shirolkar Satish; N., Kale Rupali (International Journal of Applied Pharmaceutics, 2018)
Objective: Promethazine theoclate is a BCS Class II drug having anti-histaminic property and mainly used for the treatment of motion sickness and postoperative emesis. The main objective of the research work was to formulate and optimize immediate release pellets of promethazine theoclate by using the extrusion-spheronization technique to offer immediate release dosage form suitable for treatment of nausea and vomiting associated with motion sickness and post-operative conditions. Methods: Immediate release pellets of promethazine theoclate were prepared by using microcrystalline cellulose (MCC) and corn starch as filler and disintegrant respectively along with other excipients. Pellet formulation was further optimized for bulk density, disintegration time and percent drug release after 10 min. using 32 factorial design. Formulations were also characterized for drug-polymer interactions using Differential Scanning Calorimetry (DSC), surface morphology by Scanning Electron Microscopy (SEM) and other physicochemical properties. Results: Optimised pellet formulation contains 2.5:4.5:1 ratio of MCC: Corn Starch: Drug and spheronization time of 60 seconds showing highest percent yield of 78% and immediate drug release of 100.52Â±0.65% after 10 min. Conclusion: Promethazine theoclate pellets formulated in this study can serve as an alternative to tablet dosage form which can give immediate drug release for treatment of motion sickness and postoperative emesis.